A Tertiary Level of Understanding in Qumran Interpretive Texts Discoverable Through Cascading Stichwörter - Katzin, David (Journal of ancient Judaism, 2015)
This study is premised on the understanding that the authors of the Qumran Pesharim believed that rare words and word combinations held special-contextual meaning when found in sacred texts. In support of this concept it is shown that Pesher uses an exegetical technique in which scriptural verses identified through rare words contained within them, and which are lexically associated with the lemma through Stichworter, are themselves used to provide additional keywords. Through these keywords subsequent verses containing other rare or conspicuous words are identified which, although not directly associated with the lemma, are incorporated into the interpretation. This process could be repeated multiple times, i. e., cascading Stichworter, in order to reveal a desired interpretation. In the cases presented, this very elegant hermeneutical method has the key benefit of explaining in an objective way not only the relationship between the lemma and the gloss but also the narrative flow of the gloss itself. Most importantly, it also provides a third level of understanding to the text: 1) lemma 2) gloss and 3) a newly revealed level consisting of the community's dogma, theological underpinnings, and kerygma. Further, this hermeneutical method allows for the understanding that the interpretation promulgated was revealed through the Word (davar) of God, based on divinely placed markers which would alert the inspired-understanding reader to pay attention to their surrounding context and then make the required connections. This method is illustrated first in its simplest form with the use of the basic building blocks of this technique to contemporize scripture. Ultimately, it is shown that Pesher carries this technique a step further by using these units of hermeneutics to build on one another into what can be understood as a cascade of Stichworter and word crafting which is presented in increasing levels of intricacy.